2017
DOI: 10.1177/1369433217737119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of assembling location on the performance of precast concrete beam under impact load

Abstract: With incorporation of assembling joints, precast concrete beams could behave very differently in resisting both static and dynamic loads in comparison to conventional reinforced concrete beams. With no research available on the dynamic behavior of precast concrete beams under impact load, a combined experimental and numerical study is conducted to investigate the dynamic response of precast concrete beams under impact load. The results were also compared with reinforced concrete beams. Four groups of concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, the direct method to measure impact force has been used in most impact tests (Fujikake et al, 2009; Kishi et al, 2002; Pham et al, 2018; Tachibana et al, 2010; Yan et al, 2018; Zhao et al, 2017). The impact force is recorded by load cells, which can be either strain gauge type (Dey et al, 2014; Isaac et al, 2017; Yoo and Banthia, 2017) or piezoelectric type (Ulzurrun and Zanuy, 2017; Wang et al, 2019).…”
Section: Experimental Impact Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the direct method to measure impact force has been used in most impact tests (Fujikake et al, 2009; Kishi et al, 2002; Pham et al, 2018; Tachibana et al, 2010; Yan et al, 2018; Zhao et al, 2017). The impact force is recorded by load cells, which can be either strain gauge type (Dey et al, 2014; Isaac et al, 2017; Yoo and Banthia, 2017) or piezoelectric type (Ulzurrun and Zanuy, 2017; Wang et al, 2019).…”
Section: Experimental Impact Testsmentioning
confidence: 99%
“…The impact force is recorded by load cells, which can be either strain gauge type (Dey et al, 2014; Isaac et al, 2017; Yoo and Banthia, 2017) or piezoelectric type (Ulzurrun and Zanuy, 2017; Wang et al, 2019). The load cell can be placed between the drop-weight and the tested specimen (Pham and Hao, 2016; Pham et al, 2018; Wu et al, 2016) or embedded at the rear of an impact head (Fujikake et al, 2009; Lee et al, 2018; Yan et al, 2018; Zhou et al, 2019) as shown in Figure 2. An investigation on the effects of load cell location and mass distribution of drop-weight on impact force has been reported in (Li et al, 2019b).…”
Section: Experimental Impact Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Failure behavior of an RC column under mid-span impact load [124] areas may also be subjected to impact loads arising from the falling objects and rocks. Hence, many researchers have attempted in the literature investigating the impact forces, structural responses, and failure behaviors of RC beams analytically [2,[159][160][161][162][163][164], numerically [1,[165][166][167][168][169][170][171][172][173][174][175][176], and experimentally [18,20,166,[177][178][179][180][181][182][183][184][185][186][187] under low-rate [1,2,171,175,185,187] and relatively high rate [188][189][190][191] impact loads by focusing on the influence of the structural...…”
Section: Beams and Slabs Subjected To Impact Loadsmentioning
confidence: 99%